Room temperature production of graphene oxide with thermally labile oxygen functional groups for improved lithium ion battery fabrication and performance. Issue 16 (1st April 2019) - Qin, Jiadong; Zhang, Yubai; Lowe, Sean E.; Jiang, Lixue; Ling, Han Yeu; Shi, Ge; Liu, Porun; Zhang, Shanqing; Zhong, Yu Lin; Zhao, Huijun
Abstract : We report a room-temperature synthesis method to produce graphene oxide with thermally-labile oxygen functional groups. Abstract : Graphene oxide (GO) has drawn intense research interest over the past decade, contributing to remarkable progress in its relevant applications. The chemical production of GO, however, is challenged by destructive and slowly propagating oxidation, especially for large flake graphite. Herein, we report a simple but effective method to produce well-oxidized and less defective GO by chemically oxidizing commercially available expandable graphite at room temperature (25 °C). Compared to natural graphite with similar flake sizes, expandable graphite afforded faster complete oxidation under the same oxidizing conditions. In addition, chemical oxidation at room temperature, relative to that at higher temperatures (35 and 45 °C), resulted in a reduced defect concentration in GO. Furthermore, the GO derived from the oxidation of expandable graphite at room temperature exhibited superior electrical conductivity after mild thermal treatment at 150 °C. Considering the energy-saving in both GO synthesis and reduction, the low temperature GO conversion process can be easily integrated into many other electroconductive applications. As a proof of concept, we achieved a good LiFePO4 (without carbon-coating) cathode formulation with our GO, which contributed as a 2D binder (before annealing), and obtained a conductive cathode with improved capacity and high rate performance after mild thermal annealing at 150 °C.